Metacognitive Awareness of Reading Strategy Use by English Language Teaching Students in Turkish Context: Sakarya University Sample - Orhan Kocaman; Semih Beşkardeşler (Sakarya University, 2016)
Reading is a complex cognitive activity that is not an inherently natural process unlike speaking and listening. A child can learn how to speak and listen without any formal instruction whereas reading needs to be taught to be learned. Therefore, a number of studies have been conducted on the use of reading strategies by English language learners (ELLs) in both English as a foreign language (EFL) context and English as a second language (ESL) context. Hence, with the purpose of looking at the issue from a different perspective, the current study aimed to investigate on students' metacognitive awareness of reading strategy use and to determine what types of reading strategies are used by the students of English Language Teaching (ELT) Department at a state university. 122 students ranging from 1st grade to 4th grade at ELT department of Sakarya University participated in the study. The Metacognitive Awareness of Reading Strategies Inventory (MARSI) was used to collect data regarding the reading strategies that ELT students use. Based on the findings, 4th grade students were reported to use reading strategies more than the other grades. Also, it was determined that the participants irrespective of their grade showed tendency towards global reading strategy use more than problem-solving and support reading strategies. Furthermore, there was a significant difference in global and support reading strategy use between male and female participants of the study.